The Effects of the European Economic and Monetary Union (EMU)on National Fiscal Sustainability - Mongelli, Francesco (IMF Working Papers; Working Paper ;, 1996)
This paper presents a methodology to analyze the responsiveness of fiscal sustainability to the 'endogenous fiscal discipline' that will be strengthened by the EMU. This discipline arises in response to the harmonization of tax systems, the loss of control of current and prospective money financing, and the deepening of financial market-based discipline. The model used in this paper is a generalization of Blanchard's (1984) model, in which the interest rate is determined endogenously. This provides the framework to analyze more features of the linkage between sustainability and endogenous fiscal discipline. This paper also presents a new intratemporal fiscal sustainability index.